The Impact of Sub-maximal Exercise on Neuropathic Pain, Inflammation, and Affect Among Adults With Spinal Cord Injury: A Pilot Study - Todd, Kendra R.; Van Der Scheer, Jan W.; Walsh, Jeremy J.; Jackson, Garett S.; Dix, Gabriel U.; Little, Jonathan Peter; Kramer, John L. K.; Martin Ginis, Kathleen A. (Frontiers in Rehabilitation Sciences, 2021)
Abstract Introduction: Persons with spinal cord injury (SCI) often report high levels of neuropathic pain (NP) and poor well-being, which may result from increased inflammation. This study examined the impact of sub-maximal aerobic exercise on NP, inflammation and psychological affect among adults with SCI. Methods: Eight active adults with tetraplegia (n-4, AIS A-C) and paraplegia (n=4, AIS A-C) performed 30-minutes of arm-crank aerobic exercise and reported their ratings of perceived exertion (RPE) each minute. Measures of NP, affect, and inflammatory cytokines (IL-6, IL-10, IL-1ra, TNF-α) were taken pre- (T0), immediately post-(T1), and 90-minutes post-exercise (T2). Results: NP decreased between T0 and T1 for tetraplegics (-60%, d=0.47; CI= -0.32,2.02) and paraplegics (-16%,d=0.15; CI=-0.30,0.90). Correlations between change in cytokines and change in NP were medium-to large for tetraplegics (rs ranged from -0.820 to 0.965) and paraplegics (rs ranged from -0.598 to 0.833). However, the pattern of correlations between change in cytokines and affect was inconsistent between groups. Lower baseline levels of IL-1ra predicted greater decreases in NP immediately post exercise (r=0.83, p=0.01). Conclusion: Sub-maximal exercise can positively impact NP for some persons with SCI. Further experimental research should identify the optimal exercise intensity to reduce NP for persons with SCI, in addition to understanding biomarkers which may predict changes in NP. This study was registered prior to enrollment of the first participant on ClinicalTrials.gov (NCT03955523).